Measured behaviour of a memristor‐based tuneable instrumentation amplifier. Issue 15 (14th June 2022) - Yang, Fan; Serb, Alexander; Prodromakis, Themis
Abstract: A memristor‐based tuneable instrumentation amplifier whose gain value can be adjusted by memristor is implemented and measured. While memristive devices are suitable for implementing reconfigurable circuit designs, their non‐linear characteristic and parasitic capacitance can impact performance. In this work, an instrumentation amplifier is built on breadboard using off‐the‐shelf OpAmps and packaged memristor devices and its performance is assessed. Results are compared with an identical design that preplaces memristors with resistors (losing reconfigurability in the process), to reveal the effects arising from the memristor's characteristics. Effects on frequency response, common mode rejection ratio (CMRR) and total harmonic distortion plus noise (THD+N) are observed. The memristor‐based instrumentation amplifier begins to be affected by the non‐linearity of the device only when the base OpAmps have a THD value below 0.3%. The bandwidth of the instrumentation amplifier is limited by the parasitic capacitance of memristors, and CMRR has small variation when using memristor to replace the original gain resistor. The THD+N value is large compared with identical design, but it is also found that by applying multiple memristors the increasing of THD+N can be relieved.